Jakob Andreae'nin vaazlarında Türk imgesi - Kurdam, Emre (My University, 2020)
Jakob Andreae'nin Vaazlarında Türk İmgesi adlı çalışmada, Protestan teolog Jakob Andreae'nin 1568 yılında yayımladığı Türkler Hakkında On Üç Vaaz adlı eseri Türk imgesi bağlamında incelenmiştir. Yazar söz konusu eserinde aynı yıl verdiği on üç Türk vaazını bir araya getirmiştir. Çalışmada eserin incelenmesinin yanı sıra Türk imgesi ve Türk vaazları da ele alınmış ve Andreae'nin kapsamlı bir biyografisine de yer verilmiştir. Eserin incelenmesinin sonucunda ise yazarın Türk karşıtı bir propaganda eseri ortaya koyduğu tespit edilmiştir. Türklerle ilgili aynı olumsuz kavramları vaazlarında sık sık tekrarlayan Andreae, toplum algısında Türklerin zalim, despot ve düşman olarak yer etmesini amaçlamıştır. Yazar ayrıca Türklerin Tanrı'nın cezası olarak gönderildiğini belirterek Hristiyan cemaati tövbeye sevk etmek istemiştir. Türkleri Katolik Kilisesi'ne karşı verdiği mücadelede silah olarak kullanan yazar, Türklerin ceza olarak gönderilmesinin sebepleri arasında Katolik Kilisesi'nin putperestliğini ve Hristiyan cemaatin günahlarını göstermiştir. Toplumu Türklerin olumlu yönlerine kanmamaları konusunda da uyaran Andreae, böylece onların Türklerin dinine ve yönetimine sıcak bakmasını engellemek istemiştir. Yazar Türklerle ilgili görüşlerinde genellikle döneminin hâkim Lüteryan söyleminden ayrılmamış ve eseriyle bu söylemi yaymaya çalışmıştır.

In the study titled Turkish Image in the Sermons of Jakob Andreae, the Protestant theologian Jakob Andreae's Thirteen Sermons on the Turks, published in 1568, was examined in the context of the Turkish image. In his work, the author brought together thirteen Turkish sermons he gave in the same year. In addition to the study of the work, the Turkish image and Turkish sermons were also discussed in the study, and a comprehensive biography of Andreae was also included. As a result of the examination of the work, it was found that the author produced an anti-Turkish propaganda work. Reiterating the same negative concepts about Turks in his sermons, Andreae aimed to place Turks as tyrants, despots and enemies in the perception of society. The author also wanted to make the Christian community repent, stating that the Turks were sent as the punishment of God. The author, who used the Turks as a weapon in his struggle against the Catholic Church, showed the idolatry of the Catholic Church and the sins of the Christian community among the reasons why the Turks were sent as punishment. Andreae also warned the society that they should not be fooled by the positive aspects of the Turks, and thus wanted to prevent them from being sympathetic to the religion and administration of the Turks. In his views on Turks, the author generally did not deviate from the dominant Lutheran discourse of his time and tried to spread this discourse with his work.
Keywords: Alman dili ve edebiyatı; Alman Edebiyatı; German philology; Image of the Turks; Turkish Image; Turkish sermon; Turks; Türk İmajı; Türk İmgesi; Türk vaazı; Türkler German Literature